Pengaruh Penerapan Model Pembelajaran Aptitude Treatment Interaction (ATI) Berbantuan Ular Tangga terhadap Peningkatan Kemampuan Berpikir Kritis Matematis Siswa - Amalia, Fazrina; Izzati, Nurma; Sukmaangara, Bayu (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This study aims to examine the effect of the Aptitude Treatment Interaction (ATI) learning model assisted by the snakes and ladders game media on students' critical mathematical thinking skills. The background of this study is the low critical thinking skills due to the dominance of traditional learning methods that are less varied and the minimal use of interesting media. The ATI model adjusts the learning approach to the characteristics of students, while the snakes and ladders game creates a fun and interactive learning atmosphere. This study uses a quantitative approach with a quasi-experimental design of the pretest-posttest control group type. The sample consisted of 57 grade VIII students selected by cluster random sampling from a population of 419 students, then divided into experimental and control groups. The treatment was given for eight meetings. The instrument used was a mathematical critical thinking ability test. The results of the Mann-Whitney test showed a significance value of 0.000 (p <0.05), which means that there is a significant effect of the application of the ATI model assisted by the snakes and ladders media on improving students' critical thinking skills. The effect size value of 0.522 indicates that the effect is quite large. This study has novelty because it integrates the ATI model with snakes and ladders media, which has never been studied before in the context of mathematical critical thinking skills. This model can be an alternative effective and interesting learning strategy in mathematics learning.